U.S. Evidence on Linear Feedback from Money Growth Shocks to Relative Price Changes, 1954 to 1979 - McGarvey, Mary G. (The Review of Economics and Statistics, 1985)
Evidence is provided on the allocative effects of monetary policy by estimating the extent to which money growth shocks affected individual relative prices from 1954 to 1979. Building on Geweke's (1982) feedback measure, the paper presents estimates of monetary feedback decomposed by frequency to allow monetary policy's short-run effects to differ from its longer-run effects. The results suggest that monetary feedback from 1954 to 1970 differs from the latter period in both magnitude and patterns across frequencies. The 1970s data suggest monetary variation had a greater overall effect and this effect was more concentrated at lower frequencies.